Adaptation of Rural Tuvans to Urban Life in Kyzyl in the 1960s–1980s - Dorzhu, Zoya Yu.; Shirap, Regina O. (The New Research of Tuva, 2025)
The article analyzes the specific features of adaptation among rural residents of Tuva who migrated to the republic’s capital, Kyzyl, in the 1960s–1980s. It examines the factors driving migration, migrants’ attitudes toward Kyzyl, and their impressions of urban life. The study is based on an analysis of in-depth interviews conducted with eight ethnic Tuvans who moved from rural areas to Kyzyl during that period.Following Tuva’s incorporation into the USSR in 1944, the city of Kyzyl became the center of industrial, economic, and cultural development in the republic. This was reflected in a rapid increase in the urban population, primarily due to the arrival of Russian-speaking specialists from other regions of the RSFSR. Alongside the transformations in the cities, changes also occurred in the lives of the rural Tuvan population: living conditions improved, and their cultural and educational levels rose.The research found that, for most rural residents, trips to Kyzyl represented significant events filled with impressions of encountering urban lifestyles. The first visits to the capital usually took the form of family trips and were perceived as ceremonial and long-awaited occasions, leaving a vivid mark on cultural experience and worldview. Rural youth aspired to receive education in the capital, yet they did not demonstrate a pronounced desire for relocation or deeper integration into urban life. One of the major obstacles to such integration was the system of state job placement, which assigned graduates to rural employment according to their acquired qualifications after completing their education.
Keywords: adaptation; Kyzyl; Tuvan ASSR; rural area; rural resident; educational migration; Tuvans